Assessment of hyaluronic acid and DMSO influence on low-temperature tissue damage course: an experimental model - Gurina, Tetiana; Kovalov, Gennadiy; Poliakova, Hanna; Naumova, Olga; Markovsky, Volodymyr; Seliuta, Anatolii (Problems of Cryobiology and Cryomedicine, 2026)
The research performed a local histological assessment of tissue tolerance of a solution containing hyaluronic acid, as well as its effect on the course of the inflammatory process aft er low-temperature skin damage was investigated. The safety of using a 1% solution of high molecular weight hyaluronic acid with the addition of 5% dimethyl sulfoxide (DMSO) and its effect on the inflammation development was studied using a model of low-temperature tissue injury based on the results of clinical observation, planimetric and histological studies. Additionally, the effect of 1% solutions of high molecular weight (> 2,000 kDa) and low molecular weight (10—100 kDa) hyaluronic acid on the inflammatory process aft er low-temperature tissue injury was comparatively explored. According to the results of the histological study, no morphological signs of toxic or other negative effects of subcutaneous administration of a 1% solution of high molecular weight hyaluronic acid with the addition of 5% DMSO on tissues were found. Comparison of the effects of cryoprotective solutions on the course of the wound process after low-temperature tissue damage revealed the differences both by the severity of macroscopic signs of the inflammation and by planimetric study data. The inclusion of hyaluronic acid in the composition of the cryoprotective solution is considered a optimistic approach to reducing the concentration of DMSO in order to create solutions that can be used without a washing-out stage. Probl Cryobiol Cryomed. 2025; 35(4): 208—218